An investigation of the relationship between a computer-based method and academic performance. - Stayner, Mindy L (Investigation of the Relationship Between a Computer-based Method & Academic Performance, 2014)
The purpose of this quantitative study was to investigate the relationship between a computer-based learning (CBL) method and academic performance, controlling for independent, non-academic and academic confounding, variables of high school GPA, college GPA, marital status, number of dependents, age, gender, race, level of education, and semester enrolled. Academic performance was measured by examining the six classroom test score averages among two cohorts. One cohort received face-to-face (F2F) traditional classroom teaching methods and the other received F2F plus a computer-based learning (F2F+CBL) method. The research study sample included 170 non-traditional practical nursing (PN) students who completed the Essentials course during the spring 2009 through the fall 2012 semester terms. A block stepwise regression analysis was used to predict relationships among the dependent variable, test score averages, and the independent variables. A Pearson's correlation coefficient displayed no correlation between the CBL method and academic performance (r = .003, p = .382) and insufficient evidence to reject the main null hypothesis; however, college GPA was found to have a high correlation to academic performance (r = .501, p = .000) The results indicated that the CBL method did not influence academic performance in classroom tests, but college GPA strongly correlated to test score averages.